Fire Mountains of the Islands A History of Volcanic Eruptions and Disaster Management in Papua New Guinea and the Solomon Islands - Johnson, R. Wally (ANU Press, 2013)
Volcanic eruptions have killed thousands of people and damaged homes, villages, infrastructure, subsistence gardens, and hunting and fishing grounds in Papua New Guinea and the Solomon Islands. The central business district of a town was destroyed by a volcanic eruption in the case of Rabaul in 1994. Volcanic disasters litter not only the recent written history of both countries-particularly Papua New Guinea-but are recorded in traditional stories as well. Furthermore, evidence for disastrous volcanic eruptions many times greater than any witnessed in historical times is to be found in the geological record. Volcanic risk is greater today than at any time previously because of larger, mainly sedentary populations on or near volcanoes in both countries. An attempt is made in this book to review what is known about past volcanic eruptions and disasters with a view to determining how best volcanic risk can be reduced today in this tectonically complex and volcanically threatening region